Differences in prevalence and determinants of hypertension according to rural-urban place of residence among adults in Bangladesh - Al Kibria, Gulam Muhammed; Swasey, Krystal; Gupta, Rajat Das; Choudhury, Allysha; Nayeem, Jannatun; Sharmeen, Atia; Burrowes., Vanessa (Cambridge University Press, 2022)
This article was published in the Journal of Biosocial Science [© Cambridge University Press, 2018 ) ] and the definite version is available at: https://doi.org/10.1017/s0021932018000366 The Journal's website is at: https://www.cambridge.org/core/journals/journal-of-biosocial-science/article/differences-in-prevalence-and-determinants-of-hypertension-according-to-ruralurban-place-of-residence-among-adults-in-bangladesh/CEE16A2F7A00C916A789DC615AACAF42